Indonesia PENINGKATAN DAYA SAING PRODUK LOKAL BERBASIS E-HKI DALAM PERSPEKTIF HUKUM EKONOMI - Triyono Adi Saputro; Muhammad Saiful Islam; Shabrina Rifdah Larasati; Yokhebed Arumdika Probosambodo; Hussein Gibreel Musa (Faculty of Law, Universitas Slamet Riyadi, 2023)
The urgency of the protection of domestic products in supporting economic value and increasing market competitiveness plays a large role through the registration of intellectual property rights (E-IPR). The existence of intellectual property in providing legal security for domestic products was essential for its certainty and safety. This should be done asa precaution in anticipation of unhealthy business rivalries and a minimizing of counterfeit products in the market. The methods used in supporting this study through normative research using a constitutional and case approach. Additionally, it sustained the legal source from primary and secondary data and was analyzed using descriptive analysis methods. The purpose of research is to determine the extent to which intellectual property rights protection has played in supporting the success of domestic products in the market. In view of the high presence of domestic products, the intellectual property rights registration is required by governments and stakeholders through the creation of domestic products to ensure early legal awareness of the resulting creativity needed to protect them by intellectual property. The implementation of intellectual property e-rights (E-IPR) is part of the economic laws of development because it includes efforts to enhance and develop domestic products and thus protect the state, improve the competiting power of the product, and create social welfare.